A expressão do mundo em Merleau-Ponty: sob o eixo do prefácio e introdução da Fenomenologia da percepção - Soares, Brenda Cardoso (2019)
This dissertation aims at describing and explaining the expression of the world based on the preface and introduction of Maurice Merleau-Ponty's Phenomenology of Perception. From this proposition, it is intended to reiterate the expression of the world as inseparable from the role of the configuration of perceptual phenomena. The accomplishment of this objective follows in three stages, corresponding, respectively, to three chapters. The first, highlighting the difficulty and impossibility of the phenomenological reduction in the Husserlian key, due to the inability to suppress the expression of the world, present in all our relations with knowledge. In the second, we try to emphasize Gestalt as the example of the expression of the world, discussing how its structure and spontaneous organization expose the inadequacies of empiricist and intellectualist currents. Finally, in the third chapter, it will be possible to defend an affiliation of Merleau-Ponty's phenomenology to the transcendental tradition that does not give way to an expression of the world, but which returns the primordial co-protagonism of this expression in the configuration of the perceptive phenomenon